Development Geographic Information System for Forest Mapping in Kutai Kartanegara Regency - Salmon Salmon; Pitrasacha Adytia; Sugih Niansyah; Andriawan; Reza Andrea (TEPIAN, 2023)
The agricultural, plantation, and forestry industries that are the main choice of the population to meet household food needs and boost the community's economy are very much in line with the geographical contours of the Regency Kutai Kartanegara. A geographic information system that can provide information on position, location coordinates, forest areas, forest information in Kutai Kartanegara Regency, and paths to find the location of forest areas. A web- based Geographic Information System (GIS) is required to determine the current position and location of the forest. The waterfall method is used to build this GIS framework, which involves stages such as analysis, design, code generation, testing, and maintenance. MySQL is a database management system. PHP, JavaScript, and HTML are used to create programming languages. Bootstrap user interface implementation. Black box testing is used to verify the software. The test results show that the GIS created meets the requirements and can resolve system issues.